Gliricidia sepium as dry season feed for goat production in Nigeria - Onwuka, C.F.I. (1986)
An experiment comprising five trials was conducted during the dry season (November through April) to assess the nutritional value of dried Gliricidia sepium leaves (GRL) both fed alone and supplemented with cassava peel. The ability of the leaves to meet the N requirements of West African Dwarf (Fouts Djallon) goats was examined. Gliricidia leaves contain about 3.3% N and are available throughout the year. The dried leaves were stored through the dry season without deteriorating and they can serve as a feed reserve. Goats consumed up to 477g of GRL DM/day when the diet was supplemented with cassava peel. Nitrogen in GRL was about 58% digestible.